Epidemiological characteristics of leprosy from 2000 to 2019 in a state with low endemicity in southern Brazil - Paulo Cezar de Moraes; Letícia Maria Eidt; Alessandra Koehler; Leonardo Girardi Ransan; Maria Lúcia Scrofeneker (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Leprosy is an infectious and contagious disease caused by Mycobacterium leprae and is mainly characterized by lesions in the skin and peripheral nerves. In Brazil, it is a public health problem due to its high endemicity. However, the state of Rio Grande do Sul presents low endemicity of this disease. Objective To characterize the epidemiological profile of leprosy in the state of Rio Grande do Sul from 2000 to 2019. Methods This was a retrospective observational study. Epidemiological data were collected from the Notifiable Diseases Information System (SINAN, Sistema de Informação de Agravos de Notificação). Results Among the 497 municipalities in the state, 357 (71.8%) registered cases of leprosy in the assessed period, with an average of 212 (81.5%) new cases per year. The average detection rate was 1.61 new cases per 100,000 inhabitants. The male sex was predominant (51.9%) and the mean age was 50.4 years. Regarding the epidemiological clinical profile; 79.0% of the patients were multibacillary; 37.5% presented the borderline clinical form; 16% had grade 2 physical disability at diagnosis and bacilloscopy was positive in 35.4% of cases. As for treatment, 73.8% of the cases were treated with the standard multibacillary therapeutic regimen. Study limitations There were missing/inconsistent data in the database available. Conclusions The findings observed in this study indicate that the state presents a low endemicity profile of the disease and these results can support adequate health policies relevant to the reality of Rio Grande do Sul, inserted in a national scenario of highly endemic leprosy.